Motivasi Nelayan Bugis – Makassar Beroperasi Di Perairan Australia Studi Pulau-pulau Sembilan-Barrang Lompo-Taka Bonerate - Syamsu Alam Hamid (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
This study was conducted in nine islands (Sinjai), Lompo Barrang Island (Makassar) and islands in the Marine National Park Taka Bonerate Selayar. Data was collected through in-depth interviews and observation. Respondents were purposively determined the group leader / retainer and members of fisherman, and his wife and family fishermen catching ever held in Australia. Because the data taken in this study is qualitative. The results showed that in principle fishermen operating in Australia is significantly influenced by the demands of everyday life; Biota especially sea cucumber catches, thus high economic value and abundant numbers in Australian waters; juridical aspects, the fishing is considered the most severe sanction a burning ship and monetary penalties (not afraid of physical sanctions). Involvement retainer / investors, a key trigger splendor of fishermen to catch Australia's waterways looking for biota. From the aspect of revenue, is clearly more advantageous when compared to Australian waters Indonesia.Dari aspect for the results, it appears that the retainer ( investors ) more gain much larger than mustard and divers and the skipper. His wife and teenage children , sometimes supporting the fishermen into Australian waters, especially those residing in Sinjai and Selayar